Teaching the public debate: from the teacher training to the taught object in the classroom - Gagnon, Roxane (Swiss Journal of Educational Research, 2010)
This contribution studies the transformations of a textual genre, the public debate, during its passage through the teacher training and the classrooms. In other words, we study the impact of a teacher training device regarding oral argumentation on the teachers’ effective practices. Using methodological tools normally used to analyse class interactions, we highlight and compare the contents, the activities and the didactic devices regarding the object public debate in both contexts.